STEREOTACTIC RADIOTHERAPY FOR BASE OF SKULL PARAGANGLIOMA: CASE REPORT - IEUMWANANONTHACHAI, Nantakan; CHANSILPA, Yaowalak; PATTARANUTAPORN, Pittayapoom (The ASEAN Journal of Radiology, 2023)
Summary: We present a case of atypical skull base paraganglioma involving intrasellar, suprasellar, sphenoid sinus and nasopharyngeal area. The patient presented with right-sided headache and tinnitus. Stereotactic Radiotherapy was selected to be the method of treatment for this patient because of the site of the tumor and the critical normal surrounding structures. The result showed satisfactory symptomatic improvement even if complete tumor involution did not occur.